Characterization and quality of compost produced and marketed in Rupa Rupa-Huánuco - Bailón-Rojas, Marlon Ricardo; Florida-Rofner, Nelino (Enfoque UTE, 2021)
Cocoa and coffee are important crops in the area and are managed under organic production standards, and the use of organic fertilizers is high, especially compost. For this reason, physical-chemical indicators were evaluated, and the quality of the compost produced with different inputs and marketed in the Rupa Rupa district, Huánuco-Peru region, was determined. It is a non-experimental correlational investigation with statistical adjustment of completely randomized, the treatments are the identified compost: Alborada compost (CAL), M&F Organic compost (CMF), municipal waste compost (CML), compost from the Divisoria Cooperative (CCD) and formulated commercial compost (CCF). Physical (humidity) and chemical indicators (ashes, pH, MO, N, P2O5, K, Ca, Mg, Na, Cu, Fe, Mn and Zn) were evaluated and the quality was determined according to the Colombian technical standard (NTC 5167) , the Chilean official standard (NOCh 2880) and the quality standards of the World Health Organization (OMS). The Results show no differences in the physical and chemical indicators, except for the N levels and according to the NTC and the OMS correspond to good quality compost and the NOCh classifies them as medium quality compost. In conclusion, the compost evaluated are of medium quality and the standard that best determines the quality is the NOCh, which can be applied in countries that do not have a specific standard that determines the quality of the compost.